Etika Bisnis Islam: Konsep dan Implementasi pada Pelaku Usaha Kecil. - Amalia, Fitri (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2014)
Islamic Business Ethics: Concept and Implementation on Medium Small Enterprise. This study is aimed at determining how the concept and application of Islamic business ethics for small businesses (SMEs). The purpose of this study is to determine how the concept of Islamic business ethics and how its implementation for SMEs. Research conducted in the form of descriptive analysis. The results showed that Kampoeng Creative, Bazar Medina and SMEs in the environment of UIN Jakarta has implemented a business ethics of Islam, both by employers and employees. In conducting its business and activities, entrepreneurs have to understand and implement the principles or values based on Islam values acoming from the Qur’an and Hadith. The implementation of Islamic business ethics comprises four aspects : principles, management, marketing/advertising and product / price DOI:10.15408/aiq.v6i1.1373